Self-Regulation as a Factor in the Realization of Work Engagement - Cokorda Istri Agung Mesha Saraswati Parsama; Dede Kristin; Najwa Ully Ni'mah; Belva Afsyari; Rahmah Hastuti (Psikostudia : Jurnal Psikologi, 2025)
The rapid advancement of digitalization and the emergence of Industry 5.0 have introduced new challenges in the workforce, including rising unemployment rates among university graduates and a widening skills gap. One crucial competency to navigate this dynamic work environment is self-regulation, which is believed to enhance employee work engagement. The present study endeavors to investigate the correlation between self-regulation and work engagement among employees at Company X. A quantitative correlational approach was employed, involving 168 participants selected through purposive sampling. The instruments used were the Short Self-Regulation Questionnaire (SSRQ) and the Utrecht Work Engagement Scale (UWES-9). Spearman correlation analysis revealed a significant positive relationship between self-regulation and work engagement (ρ = 0.406; p < 0.001), with the correlation categorized as moderate. These findings indicate that employees with higher self-regulation abilities tend to exhibit higher levels of work engagement. The results support the importance of developing self-regulation as a strategic means to enhance employee involvement and performance in the modern workplace.Perkembangan era digital dan transformasi industri 5.0 menciptakan tantangan baru dalam dunia kerja, termasuk meningkatnya tingkat pengangguran lulusan perguruan tinggi dan kesenjangan keterampilan di kalangan tenaga kerja. Salah satu kompetensi penting untuk menghadapi tantangan ini adalah kemampuan regulasi diri, yang diyakini dapat meningkatkan keterlibatan kerja karyawan. Penelitian ini bertujuan untuk mengetahui hubungan antara regulasi diri dan keterlibatan kerja pada karyawan di Perusahaan X. Penelitian menggunakan pendekatan kuantitatif korelasional dengan 168 partisipan yang dipilih melalui teknik purposive sampling. Instrumen yang digunakan adalah Short Self-Regulation Questionnaire (SSRQ) dan Utrecht Work Engagement Scale (UWES-9). Hasil analisis korelasi Spearman menunjukkan adanya hubungan positif yang signifikan antara regulasi diri dan keterlibatan kerja (ρ = 0,406; p < 0,001), dengan kekuatan hubungan berada pada kategori sedang. Temuan ini mengindikasikan bahwa semakin tinggi kemampuan regulasi diri yang dimiliki karyawan, semakin tinggi pula tingkat keterlibatan mereka dalam pekerjaan. Hasil ini mendukung pentingnya pengembangan regulasi diri sebagai strategi untuk meningkatkan keterlibatan dan kinerja karyawan di era kerja modern.